Reverse blocking IGCT optimised for 1 kV DC bi‐directional solid state circuit breaker. Issue 12 (1st December 2015) - Vemulapati, Umamaheswara; Arnold, Martin; Rahimo, Munaf; Antoniazzi, Antonello; Pessina, Davide
Abstract : This study presents the simulation and experimental results of the newly developed 2.5 kV reverse blocking‐integrated gate commutated thyristor (RB‐IGCT) which has been designed and optimised to have very low conduction losses and high turn‐off current capability for DC solid state circuit breaker (SSCB) applications. The device has been optimised through anode engineering, thickness and resistivity to achieve the required blocking capability of 2.5 kV and to have very low conduction losses below 1 kW at 1 kA, that is, the on‐state voltage drop is as low as 0.9 V at 1 kA. This study also presents the simulation and experimental results at the system level including the influence of the surge arrester (SA) which is connected in parallel to the RB‐IGCT to clamp the overvoltage and to absorb the energy stored in the system inductance at the current interruption. The influence of different voltage rating SAs and parallel combination of SAs on the switching behaviour of the RB‐IGCT has been investigated. A bi‐directional SSCB for 1 MW application based on 2.5 kV RB‐IGCT has been built successfully. The device simulations show that the results are in good agreement with the measurement results both at the device and system levels.